PENGARUH MOTIVASI EKONOMI DAN PELATIHAN BREVET TERHADAP MINAT MAHASISWA MENJADI KONSULTAN PAJAK DENGAN PELUANG KARIR SEBAGAI VARIABEL MODERASI - Ina Destiana (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to analyze the influence of economic motivation and tax brevet training on students' interest in becoming tax consultants, with career opportunities as a moderating variable. The background of this research is the low interest of accounting students in pursuing a career as a tax consultant, despite the significant career opportunities in this field. This study uses a quantitative approach with a survey method through questionnaires distributed to 100 accounting students in Yogyakarta. The sampling technique used is purposive sampling, and the data were analyzed using moderation regression analysis. The results show that economic motivation and tax brevet training have a positive and significant effect on students' interest in pursuing a career as a tax consultant. Furthermore, career opportunities significantly moderate the relationship between economic motivation and brevet training on students' interest. These findings highlight the importance of increasing awareness of economic benefits, relevant training, and promoting promising career prospects to encourage student interest in the tax consulting profession.